What Matters for In-House Tax Planning: Tax Function Power and Status - Ege, Matthew S.; Hepfer, Bradford F.; Robinson, John R. (The Accounting Review, 2021)
ABSTRACT Social hierarchy theory predicts that the power and status of an organizational function have a first-order effect on the function's ability to influence outcomes. We find that the rank of the title of the top tax executive is positively associated with tax planning after controlling for treatment effects. Our inferences remain when (1) using changes in the size of the c-suite as a shock to the relative power and status of the tax function, and (2) examining promotions and demotions in title rank. Point estimates suggest that tax function power and status are up to 2.6 times as important as tax planning resources, up to 4.0 times as important as tax function-specific expertise, and, more often than not, more important than manager fixed effects. Overall, results suggest that the power and status of the tax function is often what matters most in determining tax outcomes. JEL Classifications: H25; L22; M41.